Utilization Of The Al-Jabbar Mosque Assets Through Business Cooperation In West Java Provincial Secretariat - Sandy Riswanto; Santi Novani (Sean Institute, 2024)
The General Bureau, which is a division of the West Java provincial secretariat, is in charge of managing a number of assets that are currently utilized solely in the city core of Bandung for commercial purposes. The Al-Jabbar Mosques recently is one of the assets managed by the General Bureau, which is currently dispersed across 6 cities in West Java. In addition to serving as a place of worship, the mosque's supporting properties have the potential to be used as a place of business. The Al-Jabbar Mosque's supporting assets are currently not optimally managed. However, with proper utilization, the supporting assets of the mosque should be able to serve as a new source of income. The purpose of this study is to make recommendations on strategies for increasing retribution income by selecting the best alternative of business cooperation for utilizing the assets of the Al-Jabbar Mosques Multiple collection methods (secondary data analysis and interviews) are employed. By integrating the benefits of both quantitative and qualitative data, this strategy—known as mixed methods—allows for a greater understanding of the study issue. The Value Focused Thinking (VFT) and Analytic Hierarchy Process (AHP) method is used to develop alternatives of business cooperation and to select the best business cooperation by involving experts as decision makers, there are 3 (three) business alternatives identified namely commercial space rent, utilization cooperation, build operate transfer. The result from this research can be concluded that Al-Jabbar Mosque's prospective business cooperation is best served by asset utilization cooperation.